Analysis of Content-Based Tag on YouTube 'Brain Music' - Abdul Qudus, Zein Zayyin (Global Komunika : Jurnal Ilmu Sosial dan Ilmu Politik, 2024)
This paper presents a text analysis on 50 tags from the YouTube platform "Music Brain" using several tools which are provided by Voyant Tools (voyant-tools.org). It is expected that patterns, networks, and a comprehensive analysis of the Tags 'Music Video' would be generated. As a result, In this study, video tags are analyzed using text mining techniques and voyant tools. Although Voyant Tools is equipped with 28 tools, only five were utilized in this analysis. There are homonymous keyword tags in this study, such as 'Study,' 'Studying,' 'Concentration,' 'Focus,' 'Meditation,' and 'Relax.' Due to implementing folksonomies in Youtube Tags, make it easier for individuals or groups to find content based on common words and create duplication tags meaning